Evaluation of the marginal fit of a zirconia ceramic computer-aided machined (CAM) crown system - Baig, M.R.; Tan, K.Beng-Choon.; Nicholls, J.I. (Elsevier, 2010)
Statement of problem. The marginal fit of crowns is a concern for clinicians, and there is no conclusive evidence of any one margin configuration yielding better results than others in terms of marginal fit. Purpose. The purpose of this study was to evaluate the marginal fit with respect to gap and overhang of Y-TZP (yttria-stabilized tetragonal zirconia polycrystals) ceramic crowns and compare them with lithium disilicate pressable and complete metal crowns. The influence of margin configuration on the marginal fit was also evaluated. Material and methods. Impressions were made of premolar dies prepared with shoulders or chamfers with a 20-degree total occlusal convergence (n=30). Type IV stone dies were then distributed into test groups (n=10) for the fabrication of Cercon Y-TZP, IPS Empress II, and complete metal (noble type IV alloy) crowns. The crowns were then subjected to marginal gap and overhang evaluation at 6 designated margin locations using a computerized digital image analysis system. The data were calculated and statistically analyzed using 2-way ANOVA and Bonferroni post hoc tests (alpha=.05). Results. The overall mean (SD) marginal gap at the marginal opening for the crowns was 66.4 (42.2) mu m for Cercon, 36.6 (32.1) mu m for IPS Empress II, and 37.1 (22.3) mu m for complete metal (control). Overall mean (SD) overhang was -15.2 (47.5) mu m for Cercon, -22.1 (34.7) mu m for IPS Empress II, and 30.9 (31.3) mu m for complete metal (control). The ANOVA revealed significant effects by material and no significant effects by marginal configuration for marginal gap. There were significant differences in the marginal overhang values between the 2 margins, but no significant differences were found between the material groups for overhang. Conclusions. The Cercon system showed significantly larger (P<.05) marginal gaps than both the IPS Empress II and complete metal (control) crowns, but no significant differences were found in marginal overhang among the 3 material groups. There was no significant difference in marginal gap between the 2 margin configurations, namely, chamfer and shoulder, for all test groups; however, there were significant differences (P<.05) in marginal overhang values between chamfer and shoulder margins. (J Prosthet Dent 2010;104:216-227)